Comparison of narrow-band imaging with autofluorescence imaging for endoscopic detection of squamous cell carcinoma of the tonsil - Syba, J; Trnkova, K; Dostalova, L; Votava, M; Lukesova, E; Novak, S; Kana, M; Tesarova, M; Zabrodsky, M; Plzak, J; Lukes, P (European archives of oto-rhino-laryngology, 2023)
PURPOSE: Early detection of mucosal neoplastic lesions is crucial for a patient's prognosis. This has led to the development of effective optical endoscopic diagnostic methods such as narrow band imaging (NBI) and autofluorescence (AFI). Independent of each other, both of these methods were proven useful in the detection of mucosal neoplasias. There are limited reported data comparing both methods for oropharyngeal cancer diagnostics. The aim of the study was to compare NBI and AFI endoscopic visualization of signs in identifying tonsillar squamous cell carcinoma (SCC) and assessing its extent and to determine whether the score was related to the evaluator's experience. METHODS: Patients with tonsillar SCC underwent endoscopic pharyngeal examination using NBI and AFI. Fiftyseven video sequences of examinations of lesions proven to be SCC were evaluated by three reviewers. The accuracy of determination of lesion extent and visualization of its endoscopic signs of malignancy were evaluated. RESULTS: Endoscopic visualization of tumour spread was significantly better using AFI than NBI (p = 0.0003). No significant difference was found between NBI and AFI in the visualization of endoscopic malignancy determining signs (p = 0.1405). No significant difference was found among the three reviewers in the visualization of tumour spread and for identifying malignancy-determining signs in NBI endoscopy or AFI endoscopy. CONCLUSIONS: The results show that AFI obtained better results for assessing the extent of tonsillar cancers than NBI. Both methods were proven to be equal in the visualization of endoscopic malignancy-determining signs. Both are useful even for less experienced evaluators.
Keywords: Endoscopy, Gastrointestinal; krční mandle; úzkopásmové zobrazení; lidé; Humans; Palatine Tonsil; gastrointestinální endoskopie; Carcinoma, Squamous Cell; Narrow Band Imaging; spinocelulární karcinom; optické zobrazování; Optical Imaging